Exchange Nailing for Aseptic Nonunion of the Femoral Shaft after Intramedullary Nailing - Sung-Soo Ha; Chang-Wug Oh; Jae-Wook Jung; Joon-Woo Kim; Kyeong-Hyeon Park; Seong-Min Kim (Journal of Trauma and Injury)
Purpose Although exchange nailing is a standard method of treating femoral shaft nonunion, various rates of healing, ranging from 72% to 100%, have been reported. The purpose of this study was to evaluate the efficacy of exchange nailing in femoral shaft nonunion. Methods We retrospectively reviewed 30 cases of aseptic femoral shaft nonunion after intramedullary nailing. The mean postsurgical period of nonunion was 66.8 weeks. A nail at least 2 mm larger in diameter was selected to replace the previous nail after reaming. Distal fixation was performed using at least two interlocking screws. The success of the procedure was determined by the finding of union on simple radiographs. Possible reasons for failure were analyzed, including the location of nonunion, the type of nonunion, and the number of screws used for distal fixation. Results Of the 30 cases, 27 achieved primary healing with the technique of exchange nailing. The average time to achieve union was 23.1 weeks (range, 13.7–36.9 weeks). The three failures involved nonunion at the isthmic level (three of 15 cases), not at the infraisthmic level (zero of 15 cases). Of eight cases of oligotrophic nonunion, two (25%) failed to heal, and of 22 cases of hypertrophic nonunion, one (4.5%) failed to heal. Of 11 cases involving two screws at the distal fixation, two (18.2%) failed to heal, and of 19 cases involving three or more screws, one (5.3%) failed to heal. None of these findings was statistically significant. Conclusions Exchange nailing may enable successful healing in cases of aseptic nonunion of the femoral shaft. Although nonunion at the isthmic level, oligotrophic nonunion, and weaker distal fixation seemed to be associated with a higher chance of failure, further study is needed to confirm those findings.